1990
DOI: 10.1111/j.1600-0447.1990.tb05476.x
|View full text |Cite
|
Sign up to set email alerts
|

The antidepressant potential of oral S‐adenosyl‐l‐methionine*

Abstract: S-adenosyl-l-methionine (SAMe), a naturally occurring brain metabolite, has previously been found to be effective and tolerated well in parenteral form as a treatment of major depression. To explore the antidepressant potential of oral SAMe, we conducted an open trial in 20 outpatients with major depression, including those with (n = 9) and without (n = 11) prior history of antidepressant nonresponse. The group as a whole significantly improved with oral SAMe: 7 of 11 non-treatment-resistant and 2 of 9 treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0

Year Published

1992
1992
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(35 citation statements)
references
References 21 publications
(10 reference statements)
2
33
0
Order By: Relevance
“…This significant ef fect is noticeable after 10 days of treatment, confirming previous reports of its rapid anti depressant activity [15]. In this study the de gree of average improvement according to the HAM-D-21 following SAMe treatment ap pears to be less (32%) than expected, based on the findings of previous studies by Rosen baum et al [ 13] and Kagan et al [ 15] (51 and 61 %, respectively). This discrepancy may be accounted for by the uniqueness of this popu lation, as very little is known about rates of response to treatment with antidepressants in postmenopausal women.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…This significant ef fect is noticeable after 10 days of treatment, confirming previous reports of its rapid anti depressant activity [15]. In this study the de gree of average improvement according to the HAM-D-21 following SAMe treatment ap pears to be less (32%) than expected, based on the findings of previous studies by Rosen baum et al [ 13] and Kagan et al [ 15] (51 and 61 %, respectively). This discrepancy may be accounted for by the uniqueness of this popu lation, as very little is known about rates of response to treatment with antidepressants in postmenopausal women.…”
Section: Discussionsupporting
confidence: 69%
“…There is evidence that SAMe is an effective antidepressant [12] both by paren teral and oral route. In an open trial with oral SAMe on 20 depressed outpatients, Rosen baum et al [13] observed a significant im provement in mood as well as significant neu roendocrine effects [14]. These findings are consistent with the recent observation by Ka gan et al [15] of SAMe being more effective than placebo in treating depressive symptoms among 15 inpatients with major depression.…”
Section: Introductionsupporting
confidence: 82%
“…Ginseng root is standardized on content of ginsenosides. Most of the pharmacological effects of ginseng are attributed to ginsenosides [16]. Ginsenosides have been shown to interact with numerous membrane proteins such as ion channels, transporters and receptors, which lead to a broad range of physiological activities.…”
Section: Ginsengmentioning
confidence: 99%
“…The first, Sadenosyl-L-methionine (SAMe), is proposed to have anti-depressive properties by causing elevations in dopamine and noradrenaline levels and increases in 5-HT turnover [324]. The second, St John's Wort, is proposed to be a treatment for mild depression by a) inhibiting reuptake of norepinephrine, dopamine, and 5-HT; and b) having affinity for adenosine and GABA receptors [86,325].…”
Section: Supplements (S-adenosyl-l-methionine (Same) and St John's Wort)mentioning
confidence: 99%